2017
DOI: 10.18632/oncotarget.21127
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential tissue-specific cancer biomarkers and development of cancer versus normal genomic classifiers

Abstract: Machine learning techniques for cancer prediction and biomarker discovery can hasten cancer detection and significantly improve prognosis. Recent “OMICS” studies which include a variety of cancer and normal tissue samples along with machine learning approaches have the potential to further accelerate such discovery. To demonstrate this potential, 2,175 gene expression samples from nine tissue types were obtained to identify gene sets whose expression is characteristic of each cancer class. Using random forests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 114 publications
1
12
0
Order By: Relevance
“…Affymetrix probes were mapped to the genes using the information provided in the Affymetrix database (hgu133plus2.db). We used average expression values when multiple probes mapped to the same gene 19 .…”
Section: Probe To Gene Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…Affymetrix probes were mapped to the genes using the information provided in the Affymetrix database (hgu133plus2.db). We used average expression values when multiple probes mapped to the same gene 19 .…”
Section: Probe To Gene Mappingmentioning
confidence: 99%
“…To this end, gene expression data from 181 samples from PICU within the first 24 hours were analyzed using multiple statistical testing methods to identify gene biomarkers. The gene expression profiles discovered by this statistical approach may lead to new insights into genetic biomarkers for successful septic shock diagnosis 19 . Using functional geneset enrichment analysis, we validated the known septic shock-related genes, pathways and functional groups, and identified the unexplored septic shock-related genes, and functional groups.…”
Section: Introductionmentioning
confidence: 99%
“…These findings were not confirmed in another study [ 35 ], which has shown a slight advantage of SVM. Nevertheless, both algorithms are still used for building predictive models for gene expression, and some new reports show a relative advantage of Random Forest over SVM on various sets of problems [ 36 , 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…Employing the supervised learning algorithm and RF over nine tissue types, Mohammed et al have shown successful classification between normal and cancer tissues when tissue type is specified as well as non-specified. They further identified genes as potential biomarkers and critical pathways for different tissue types ( 43 ).…”
Section: Ai In Cancer Classification and Subtype Determinationmentioning
confidence: 99%